Frederik Lange Grundtvig : folkeminder fra Lyngby sogn 1864-70 - Piø, Iørn (Copenhagen : [Dansk folkemindesamling], 1967)
Summary: Folklore collected 1864-70 by Frederik Lange Grundtvig in the Parish of Lyngby.
Offprint from Lyngby-Bogen, vol. 7, 1966.
Keywords: Grundtvig, Frederik Lange; kansanperinne; kokoelmat; perinteenkerääjät; folktradition; samlingar; traditionsinsamlare; Tanska -- Lyngby; Tanska; Danmark